Hubungan Intensitas Bermain Game Online Mobile Legend dengan Self Regulated Learning Siswa SMAN 1 Prajekan di Bondowoso - Bayu Dwi Maulana Putra; Iin Ervina; Anggraeni Swastika Sari (Jurnal Psikologi, 2023)
Self Regulated Learning is a process for individuals to regulate their learning patterns independently to gain knowledge, such as goal setting, planning, learning strategies, self-strengthening and self-instruction. Self-regulated learning is really needed by students to regulate themselves in improving their learning abilities. This research aims to determine the relationship between the intensity of playing mobile legend online games and the self-regulated learning of students at SMAN 1 Prajekan in Bondowoso. The type of research used is quantitative research with correlational methods. The population in this study was 168 students of SMAN 1 Prajekan with a sample of 122 students. The sampling technique uses purposive sampling. Data collection uses Google Form and distribution via WhatsApp messages. The scale used is the Online Game Playing Intensity scale which was adapted from Nugroho's (2020) research (18 items; α= 0.920). The Self Regulated Learning Scale was adapted from research by Sari & Linsiya (2022) (14 items; α= 0.698). The results of this study show that there is a significant negative relationship between the intensity variable of playing mobile legend online games (X) and the self-regulated learning variable (Y) of (r = -0.461; p < 0.05). This means that the higher the intensity of playing mobile legend online games, the lower the students' self-regulated learning, and vice versa